Picture perfect practice : a self-training guide to mastering the challenges of taking world-class photographs - Valenzuela, Roberto (Voices that matter, 2012)
The author presents his advice and practice routines for composing and capturing photographs of people, illustrated with examples from his own practice sessions and from his extensive work photographing weddings around the world.